The virtualics and strategic self‐management as tools for sustainable development - Paulauskas, Stasys; Paulauskas, Aleksandras (Technological and Economic Development of Economy, 2008)
The methodological problems and practical decisions related to introduction of sustainability culture into life of the State of Lithuania are presented in this article. The methodology, models and decisions of the article are based on long‐term researches and their implementation into governance, economy and education. The methodology of virtual modelling enables to raise certainty of development models of the country. Theoretic decisions of Strategic Self‐management (SS) enabled to synthesise purposive homogenous model of SS of the State, the implementation of which could give a substantial push for decision accumulating problems of governance. This decision is related to implementation of self‐organisation in each level of governance on the ground of natural SS cycle. The qualitative system of SS is developing by purposively created Public Institution Strategic Self‐Management Institute and its innovations works “Strategic Self‐Management” (ISSN 1648–5815). SS of enterprises, economy branches and the State are modernised on the ground of this model. The decisions of sustainability culture improvement in maritime and energy economies, problems and results of its implementation are presented.Virtualika ir strateginė savivalda kaip darnaus vystymosi įrankiaiSantrauka. Straipsnyje pristatomos da. rnos kultūros įgyvendinimo Lietuvos valstybėje metodologinės problemos ir jų praktiniai sprendimai. Ši metodologija, modeliai ir sprendimai pagrįsti ilgalaikiais moksliniais tyrimais bei jų praktinio įgyvendinimo valstybės savivaldoje, ūkinėje veikloje ir švietime patirtimi. Virtualiojo modeliavimo metodologija leidžia didinti šalies raidos modelių apibrėžtumą. Teoriniai strateginės savivaldos sprendiniai padėjo susintetinti vienalytį visuomenės strateginės savivaldos modelį, kurio įgyvendinimas galėtų padėti sprendžiant susikaupusias savivaldos problemas. Šis sprendinys susietas su natūralaus strateginės savivaldos ciklo įgyvendinimu kiekvienu visuomenės savivaldos lygmeniu. Kokybinė strateginės savivaldos sistema yra tobulinama tuo tikslu įsteigtame Strateginės savivaldos institute ir jo leidžiamame naujadaros leidinyje „Strateginė savivalda“ (ISSN 1648-5815). Remiantis šiuo modeliu, tobulinama įmonių, ūkio šakų ir valstybės strateginė savivalda. Straipsnyje pristatomos darnos kultūros tobulinimo jūrų ir energetikos ūkyje problemos, sprendimai ir jų įgyvendinimo rezultatai.Reikšminiai žodžiai: darnos kultūra, naujadara, virtualika, virtualus modeliavimas, strateginė savivalda, atsakingoji energetika, vėjo energetikos klasteris.First published online: 21 Oct 2010